SIKAP KERJA MAHASISWA DALAM PELAKSANAAN PRAKTEK GASTRONOMI DI JURUSAN ILMU KESEJAHTERAAN KELUARGA PERIODE JULI-DESEMBER 2016 - Rahimah Rahimah; Asmar Yulastri; Anni Faridah (Journal of Home Economics and Tourism, 2018)
This study aimed to describe the attitude of student work in the lecture Gastronomi practice in the Department of Family Welfare period from July to December 2016 in terms of discipline, responsibility, self-confident, and caring. This type of research is descriptive quantitative research. The study population is students who follow courses in Gastronomi Family Welfare Science July-December period of 2016 amounted to 78 people. The sampling technique Proportional Random Sampling technique and the entire population is used as a sample. Data was collected using a questionnaire (questionnaire), using a Likert scale which has proven validity and reliability. Furthermore, the data were analyzed with descriptive analysis malalui categorize assessment method based on mean scores and the percentage of votes. The research the work attitude of students in the lecture gastronomi practice in the Department of Family Welfare period from July to December 2016 include a low category as much as 60.25%.Keywords: Student Work Attitude, Practice, Gastronomi, Ilmu KesejahteraanKeluarga